Blood Flow in Large Femoral Artery - Alsubaie, Mariam Mohammed (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
The present master research project entitled, Blood Flow in Large Femoral Artery, has beenspread over in three chapters. Chapter-1, gives the information and overall development of Biofluid Mechanics. This chapter further deals with basic definitions, governing equations of variousmodels, different types of fluids and set of Magneto-hydrodynamic equations. In this chapter wehave also discussed about the importance of the subject, cardiovascular system, distribution ofblood volume and difference between anatomy and physiology.The aim of the chapter-2 is based on the interest of today's research in Bio-fluid dynamics, moreand more dedicated to accurate modeling of the blood flow characteristics. It became evident thatblood is a complex fluid, with properties depending on many factors, not limited to shear rateand hematocrit. In this chapter we have discussed in details about the blood rheology and bloodvessels because it is very important to understand the blood flow in the artery. Few properties ofblood flow also have been discussed in this chapter.Chapter-3, presents a theoretical model of oscillatory blood flow in circulatory rigid tube. Theassumptions of a Newtonian rheology is considered and blood flow is described by the NavierStokes equations with specific term pressure gradient and boundary conditions. In this chapterwe have got the analytical solution of the problem in terms of velocity and flow rate. The mainaim of this chapter is, how the fluid dynamics play an important role in the understanding of thehuman circulatory system. This type of blood flow problem occurs in the human body in thecase of diseased artery